2019
DOI: 10.1016/j.tipsro.2019.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Advanced practice: An ESTRO RTTC position paper

Abstract: European Society for radiotherapy and oncology (ESTRO) committee The ESTRO Radiation Therapist committee (RTTC) is made up of 14 representatives (including 2 elected members of the RTT alliance) working as radiation therapists (RTTs) in clinical departments and academic institutes. The role of the RTT in Europe has been described in previous ESTRO documents, with clear guidelines and definitions as to the educational standards required of an undergraduate practitioner (level 6) [1] and advanced/specialist prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(48 citation statements)
references
References 35 publications
1
47
0
Order By: Relevance
“…These role extensions can provide cost-effective utilisation of the radiotherapy workforce. 9 Although skill mix initiatives are widespread and can enhance the job satisfaction of staff involved, 10 there is limited evidence of impact upon service quality and patient outcomes. 11 Against a backdrop of increasing demand and sustained shortages within the consultant clinical oncologist workforce, the Department of Clinical Oncology at Northampton General Hospital (NGH) NHS Trust developed a skill mix initiative under the leadership of their clinical radiotherapy lead.…”
Section: Introductionmentioning
confidence: 99%
“…These role extensions can provide cost-effective utilisation of the radiotherapy workforce. 9 Although skill mix initiatives are widespread and can enhance the job satisfaction of staff involved, 10 there is limited evidence of impact upon service quality and patient outcomes. 11 Against a backdrop of increasing demand and sustained shortages within the consultant clinical oncologist workforce, the Department of Clinical Oncology at Northampton General Hospital (NGH) NHS Trust developed a skill mix initiative under the leadership of their clinical radiotherapy lead.…”
Section: Introductionmentioning
confidence: 99%
“…Increasingly complex IGRT practices places greater demands on RTT training to ensure accurate and precise treatment delivery, including calls for advanced practice RTTs to enable adaptive radiotherapy [20,21]. However, several studies have demonstrated that specialized training enables adaptive radiotherapy decision making (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In radiation oncology centres specifically, radiation therapists (RT) performing advanced practitioner roles were introduced in the United Kingdom at the turn of the century [1] , and in the Canadian province of Ontario shortly after [2] . Discussion papers, frameworks elaborating expectations of practice and formal recognition pathways exist across multiple jurisdictions [3] , [4] , [5] , [6] , [7] , [8] , and many reports of local practice outcomes as a result of radiation therapy advanced practitioner implementation have been published during the last two decades [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] .…”
Section: Introductionmentioning
confidence: 99%